Low cost semi-automatic acrylic cutter and bending machine - Siti Maryam, Sharun; Muhammad Firdaus Asyraf, Abdul Halim Yap; Sharifah Hanis Yasmin, Sayid Abdullah (Blue Eyes Intelligence Engineering and Sciences Publication, 2020)
In the current market, the acrylic cutter and bending machine is mostly available in big size and equipped with advanced system processes for large industrial application. This is undesirable since the cost of the machine can be quite expensive for a small industry. This paper proposed the development of a low-cost semi-automatic acrylic cutter and bending machine to cater to the small industry requirement. The design methodology has been accomplished using engineering design method to propose a suitable design semi-automatic acrylic cutter and bending machine based on commercially available design. A 3D representation of the machine was generated with the help of Autodesk Inventor 2019 to visualize all the details concerning the semi-automatic acrylic cutter and bending machine. The semi-automatic acrylic cutter and bending machine are designed for cutting, bending, and finishing acrylic sheet in simple manual operation. The machine was fabricated using industrial material specifications such as plywood and hollow steel to ensure the effectiveness of semi-automatic acrylic cutter and bending machine. This semi-automatic acrylic cutter and the bending machine was also equipped with a table that can be adjusted to different heights. The performance of the machine was tested by cutting and bending different thicknesses of the acrylic sheet and polishing of the acrylic sheet. The results found that the semi-automatic acrylic cutter and bending machine is capable of handling the thickness of the acrylic sheet up until 5 mm in a single operation. The developed machine was able to cut the acrylic sheet up to 5 mm thickness and bend from 0 to 180 degrees. Thus, this machine could provide a highly ergonomic solution that responds to the needs of small industrial applications.